2020
DOI: 10.1108/jbim-02-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientations, marketing capabilities and radical innovation launch success

Abstract: Purpose The purpose of this paper is to develop a radical innovation launch model that shows the relationship of the market, entrepreneurial and learning orientations with each other, with radical innovation launch marketing capabilities and the subsequent effect on radical innovation launch success. It will provide practitioners with best practices and add to current marketing theory. Design/methodology/approach An online survey was done, resulting in a usable sample of 176 radical innovation launch practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 104 publications
1
21
0
Order By: Relevance
“…For them, resource diversity is not the only reason for these performance differences. Instead, one of the main reasons for this difference is the diversity of a firm's capability, as resources require the capabilities to be converted into the firm outputs (Wang and Ahmed, 2007;Morgan et al, 2009a;Cake et al, 2020). In this respect, researchers highlighted the critical role of dynamic capabilities for firm operations and performance in the marketing literature (Day, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For them, resource diversity is not the only reason for these performance differences. Instead, one of the main reasons for this difference is the diversity of a firm's capability, as resources require the capabilities to be converted into the firm outputs (Wang and Ahmed, 2007;Morgan et al, 2009a;Cake et al, 2020). In this respect, researchers highlighted the critical role of dynamic capabilities for firm operations and performance in the marketing literature (Day, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2020) suggested that the possible missing link between learning orientation and financial performance could be the relationship between knowledge internalization and international marketing performance. In addition, Cake et al (2020) found that learning orientation has an impact on radical innovation launch success through marketing capabilities. Ismail and Kuivalainen (2015) observed that firms with international scope and global scope have different levels of internal capabilities; the former relies more on founders' foreign experiential knowledge, while the latter has heterogeneous capabilities such as dynamic marketing capabilities.…”
Section: Learning Orientationmentioning
confidence: 99%
“…Market orientation refers to a firm's focus on market needs and its sensitivity to changes in the market environment. Market orientation is often an antecedent of marketing capabilities, which have been tested in many international marketing studies (Acikdilli et al, 2020;Alnawas and Farha 2020;Cake et al 2020), but market orientation in the BG context has yet to receive much attention (Øyna and Alon 2018). Relatedly, Morgan et al (2018) observed that there is insufficient interaction between the academic literature on international business and international marketing in terms of empirical research on BG firms.…”
Section: Market Orientationmentioning
confidence: 99%
“…Radical innovations are well-recognized for their importance to enable renewal and long-term business growth (Cake et al, 2020). Research on knowledge intense firms illustrates that a difference can be detected between radical and incremental innovations (Van Poucke, 2005).…”
Section: Introductionmentioning
confidence: 99%